Evaluation of the precision and accuracy of the DIPA software postural assessment protocol. (2nd October 2017) - Furlanetto, Tássia Silveira; Candotti, Cláudia Tarragô; Sedrez, Juliana Adami; Noll, Matias; Loss, Jefferson Fagundes
Abstract: To evaluate the repeatability and intra- and inter-rater reproducibility of the DIPA protocol for postural evaluation of the frontal and sagittal planes; and to evaluate the validity of the results of evaluating the spine in the sagittal plane using the DIPA software. To evaluate the intra- and inter-rater reproducibility and repeatability ( n = 16), the DIPA protocol was conducted on the individuals by three raters, by the same rater on different two occasions and by same rater twice immediately, respectively. To evaluate validity, 54 individuals underwent X-ray evaluation of the spine in the sagittal plane and the DIPA protocol. The Intraclass Correlation Coefficient, the Standard Error of Measurement (SEM) and the Minimum Detectable Change (MDC) were used to evaluate the repeatability and reproducibility; and the Pearson's correlation test, the independent t test and the Morgan–Pitman's test were used to evaluate the validity. The knee angle, sagittal and scoliotic arrows presented acceptable levels of correlation, with low SEM and MDC values. When compared to X-ray examination, the results of the DIPA software were excellent, with no significant difference, random error and similar variance between measurements. The DIPA protocol is accurate and precise, and can be used by the same or different raters.